Increasing International Corporate Sales in Digital Sales Channels, Case: International Corporate Sales of a Travel, Transportation, Logistics & Hospitality Industry - Hankivuo, Salla (My University, 2019)
Purpose - This research focuses on identifying ways to increase international corporate sales in digital sales channels. The case industry is TTLH (Travel, Transportation, logistics & Hospitality) and the case company represents the industry field of travel and transportation. Research approach - To reach the research objectives, theoretical and empirical research was conducted. Literature review represents the theoretical part of the research which focuses on studying the role of culture in B2B sales, defining the elements in the sales lead management and what is the distinction between traditional and digital sales channels. The nature of the research is qualitative, and it follows an inductive approach. Empirical research was conducted with eight interviews from six different companies. The selection criteria for the interviewed companies and for the benchmark companies were that they are international or global companies. Findings - Findings shows that the basic elements of the lead and sales processes have to be in place before succeeding in international digital sales. To have a functional and company-wide lead and sales process, the commitment of the management level, clear ownership for the processes, the culture of sharing information in all markets and getting everyone involved are required. International B2B sales through digital sales channels is recommended to start by targeting SME segments that already use digital channels naturally. Moreover, it is suggested to proceed with a narrowed and more standardized offering with SMEs than with large companies. Large companies with notable investments often require a physical presence of salespeople in the purchase process. Contributions - This research provided recommendations to the lead process of the case company. The findings of this research are not limited only for the case industry or the case company. Future work is needed to identify B2B buyer personas especially in the SME segment where the recognized growth potential lies. _________________________________________________
Keywords: B2B lead process; international digital sales channels; international lead; B2B sales process; fi=Master's Degree Programme in International Business|